Estudo comparativo entre polietileno de alta densidade, espuma de poliuretano e Amberlite XAD-2 na adsorção de hidrocarbonetos policíclicos aromáticos - Silva Junior, Fabio Vieira da (2018)
Polyciclic aromatic hydrocarbons (PAH) are compounds that present two or more condensed aromatic rings. These substances can be found in the environment, and its contamination could lead to health risks. For environmental and biological monitoring of PAH passive or active sampling could be used containing na adsorbent material. In this work, high density polyethylene (HDPE) and polyuretane foam (PUF) were compared to Amberlite XAD®-2 for adsorption of naphthalene (NAP), acenaphthylene (ACY), acenaphthene (ACE), Fluorene (FLN), phenanthrene (PHE), anthracene (ANT), and chrysene (CHR). The adsorption of PAH in these materials were studied using UV-vis spectrophotometry. The experiments were performed in batches and the amount of PAH adsorbed during the time was obtained from the concentratrion of these compounds in solution in relation to the initial concentration. The effect of chemical modifier, amount of adsorbent, and the adsorption capacity were studied. Kinetic models of pseudo first order, pseudo second order and intraparticle diffusion were applied. Adsorption experiments at constant temperature provided data for application of Langmuir and Freundlich isotherm models. Hierarchical cluster analysis (HCA) was used as a chemometric tool to evaluate the similarities and diferences of PAH adsorption behaviour among adsorbents. If the amount of adsorbents is reduced to 0.1 g no siginificant change was observed with adsorption of more than 90% of PAH, with exception of chrysene. Two behaviour were observed for adsorption capacity within the range from 0 to 180 min. From 0 to 60 min high rates were found and between 60 and 180 min low variation was observed. The pseudo second order kinetic model was applied to PAH with exception of naphthalene. The isotherms (Langmuir) presented favorable profiles for adsorption of naphthalene and anthracene in HDPE and PUF and chrysene in PUF and XAD-2. The adsorption of acenaphthylene, acenaphthene and chrysene in HDPE presented better correlations with Freundlich model. The isotherms presented favorable forms and the adsorption remained constant for the reduction of adsorbents amount, with the exception for chrysene. Using HCA similarities and differences among adsorbents were observed, with separation in different groups. HDPE and PUF could be considered as promising adsorbents due to their availability, low cost and facile adaptation and evaluation in adsorption sampling devices.